Integrated Analysis of Seismic and Well Data to Determine CO₂ Injection Zones in “W” Field of The Talang Akar Formation, Asri Basin - Ardiansyah, Muhammad Feri Edo; Lubis, Muhammad Husni Mubarak (UIR PRESS, 2024)
Asri Basin is one of the most prospective areas to store CO₂ in a CCS project in Indonesia. Previously, Asri basin was one of the most prolific oil and gas provinces in the region. This study characterizes the CO₂ injection zone in the saline aquifer reservoir by analyzing seal, storage, and injectivity. A model-based seismic inversion method was used to produce an acoustic impedance volume, which was then transformed into a porosity volume and a permeability volume. Also, analysis of seismic variance attributes was also carried out to investigate the presence of faults surrounding the seal. The results indicated that the seal quality criteria in the study area are satisfactory because no faults intersect the seal. The average distribution of porosity values in the injection target zone is 32%, with the distribution of permeability values being more than 500 mD, making the area satisfactory for CO₂ injection.